Advanced Technologies in Cardiovascular Bioengineering - Zhang, Jianyi; Serpooshan, Vahid; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents a systematic overview of the technologies currently being explored and utilized in the fields of cardiovascular tissue engineering and regenerative medicine. Considering the unprecedented rapid progress occurring on multiple technological fronts in cardiac tissue engineering, this important new volume fills a need for an up-to-date, comprehensive text on emerging advanced biological and engineering tools. The book is an important resource for anyone looking to understand the emerging topics that have the potential to substantially influence the future of the field. Coverage includes iPS stem cell technologies, nanotechnologies and nanomedicine, advanced biomanufacturing, 3D culture systems, 3D organoid systems, genetic approaches to cardiovascular tissue engineering, and organ-on-a-chip. This book will be a valuable guide for research scientists, students, and clinical researchers in the fields of cardiovascular biology, medicine, and bioengineering, as well as industry-based practitioners working in biomaterial science, nanomaterials and technology, and rapid prototyping and biomanufacturing (3D bioprinting). Examines rapidly emerging technologies in the field of cardiovascular tissue engineering; Covers state-of-the-art biomanufacturing techniques; Presents basic science and engineering concepts, coupled with clinical and translational advancements.
Part I. Cardiac development and morphogenesis -- Chapter 1. From simple cylinder to four-chambered organ: a brief overview of cardiac morphogenesis -- Chapter 2. Lineage Tracing Models to Study Cardiomyocyte Generation during Cardiac Development and Injury -- Chapter 3. Mechanisms that govern endothelial lineage development and vasculogenesis -- Part II. Cellular approaches to cardiac repair and regeneration -- Chapter 4. Remuscularization of Ventricular Infarcts Using the Existing Cardiac Cells -- Chapter 5. Allogeneic immunity following transplantation of pluripotent stem cell-derived cardiomyocytes -- Chapter 6. Vascular regeneration with induced pluripotent stem cell-derived endothelial cells and reprogrammed endothelial cells -- Chapter 7. The guinea pig model in cardiac regeneration research; Current tissue engineering approaches and future directions -- Part III. Genetic approaches to study cardiac differentiation and repair -- Chapter 8. Analyzing genetic programs of cell differentiation to study cardiac cell diversification -- Chapter 9. Recombinant Adeno-Associated Virus for Cardiac Gene Therapy -- Part IV. Bioengineering approaches to cardiovascular tissue modeling and repair -- Chapter 10. Microfabricated Systems for Cardiovascular Tissue Modeling -- Chapter 11. Bioengineering of Pediatric Cardiovascular Constructs: In Vitro Modeling of Congenital Heart Disease -- Chapter 12. Biomaterial Interface in Cardiac Cell and Tissue Engineering -- Chapter 13. Stem Cell-based 3D Bioprinting for Cardiovascular Tissue Regeneration -- Chapter 14. Creating and Validating New Tools to Evaluate the Electrical Integration and Function of hPSC-derived Cardiac Grafts in Vivo -- Part V. Clinical perspectives -- Chapter 15. Understanding the Molecular Interface of Heart Disease and COVID-19: A Data Science Approach -- Chapter 16. Clinical Application of iPSC Derived Cardiomyocytes in Patients with Advanced Heart Failure -- Chapter 17. Cell Therapy with Human ESC-derived Cardiac Cells: Clinical Perspectives.
Keywords: Biomedical engineering; Regenerative medicine; Biomaterials; Biomedical Engineering and Bioengineering; Regenerative Medicine and Tissue Engineering; Biomaterials; Cardiovascular Diseases -- therapy; Tissue Engineering -- methods; Cell- and Tissue-Based Therapy